Development of a CFD Model of Bubble Column Bioreactors: Part Two – Comparison of Experimental Data and CFD Predictions. Issue 1 (5th December 2013) - McClure, Dale D.; Kavanagh, John M.; Fletcher, David F.; Barton, Geoffrey W.
Abstract The application of computational fluid dynamics (CFD) as a tool to simulate bubble column bioreactors is investigated. A three‐dimensional model utilizing the Euler‐Euler approach is evaluated. The role of various terms, i.e., lift, drag, bubble‐induced turbulence, and volume fraction correction terms for drag, is determined. Good agreement between experimental data and simulation results was obtained by means of a single‐bubble size model provided that bubble‐induced turbulence and the reduction in drag due to the presence of other bubbles were taken into account.